Pandemi Covid-19 Dalam Risiko Masyarakat Kontemporer - Halimatuz Zahro; Sri Devi Januarifka Fitria; Yuan Amukti Palupi (Pusat Riset dan Inovasi Nasional, 2023)
The Covid - 19 pandemic is a disaster that occurs quickly and thoroughly. This pandemic affects not only health, but also the economic, cultural, social and political education fields. The existence of the Covid - 19 pandemic makes people live in conditions of risk. Society will face terrible threats such as the spread of viruses and other threats. The consequences of the emergence of the Covid - 19 virus have caused social anxiety in society. This raises serious concern because this virus is increasingly spreading, including in areas where there are few positive confirmed cases of Covid - 19 itself. There are so many threats of Covid 19 that great attention is needed for the perception of own risk in decision making. The current situation shows that society has become a risky society. Where people are at risk themselves are vulnerable people. Community life will be colored by risks that can affect society. This article tries to analyze the context of the covid - 19 pandemic in at-risk communities by using a sociological perspective of at-risk communities, especially in the covid - 19 pandemic. This Covid - 19 pandemic also shows that society is not ready to face the Covid 19 disaster which occurred as a whole and not a single country that can avoid the impact of Covid - 19. In addition, this article shows that the pandemic affects all classes in society and affects people from young to old